Expression and activity of RhoA/Rho kinase in remodeling of high blood flow pulmonary vessels. - Li, Fu-hai (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2007)
OBJECTIVE: High pulmonary blood flow induced pulmonary hypertension (PH) is often associated with increased vasoconstriction and deteriorating pulmonary artery remodeling, of which the exact mechanism has not been completely elucidated. The involvement of RhoA/Rho-kinase pathway has been demonstrated in the pathogenesis of hypoxia and monocrotaline induced PH. Thus the purpose of this study was to test whether RhoA/Rho-kinase pathway is involved in the process of high pulmonary flow induced pulmonary artery remodeling in rats